Electroglottography in the diagnosis of functional dysphonia - Szkiełkowska, A. (Eur Arch Otorhinolaryngol, 2018)
INTRODUCTION: Electroglottography (EGG) is the most commonly used method of indirect visual examination of vocal fold vibration. AIM: The study was conducted with an aim of assessing EGG quasi open quotient (QOQ(EGG)) in different functional dysphonias to develop a differential diagnosis. The second aim was to check the influence of articulation on QOQ(EGG) values. MATERIAL AND METHODS: There were 20 people without voice problems, 20 patients with hypofunctional dysphonia and 20 patients with hyperfunctional dysphonia included in the study. Electroglottography was recorded during comfortable sustained phonation of [a], [e], [i], [o], [u]. RESULTS: There were no statistically significant differences in QOQ(EGG) observed during phonation of different vowels in the control group and patients with hyperfunctional dysphonia. In patients with hypofunctional dysphonia, significantly higher values of QOQ(EGG) were observed during [a] and [e]. Both in the control and in studied groups vowel [i] was vocalized significantly quieter. CONCLUSIONS: To conclude, EGG can be useful in differential diagnosis of functional dysphonia. QOQ(EGG) is a parameter differentiating hypofunctional dysphonia from hyperfunctional dysphonia. Dissimilarities in articulation of different vowels in patients with various types of dysphonia influence values of QOQ(EGG). EGG study protocol in cases of functional dysphonia should include a comparison of [a], [e], [i] vowels.